Localization and amplification of Rayleigh waves by topological elastic metasurfaces - Zhou, Weijian (2022)
Recently, the concept of metasurface becomes a hot research topic due to its outstanding advantages compared with its bulk counterpart metamaterial, such as low propagation loss, cheap fabrication cost, compact geometrical structure, high integration level, and specifically excellent performance in wavefront manipulation. Instead of designing elastic metasurfaces for wavefront manipulation based on generalized Snell's law that have been widely studied, in this paper we focus on the topological performance of one dimensional elastic metasurface for manipulation of Rayleigh waves. We present two methods to design the topological metasurface, and several kinds of metasurfaces will be studied. We will show the existence of topologically protected interface modes in these topological metasurfaces that can realize energy localization around interfaces in the topological metasurface, and the displacement at the interface can be amplified more than two times than the input Rayleigh waves. This research may have important applications in sensitive Rayleigh wave detection, nondestructive testing, energy harvesting of surface waves and other Rayleigh wave related techniques.